Efektivitas Pelatihan di Wilayah Kerja (PDWK) TIK bagi Guru MTs di Kabupaten Bojonegoro - Ani Nur Hidayati (Balai Diklat Keagamaan Surabaya, 2021)
The purpose of this study was to analyze the effectiveness of the implementation of training in the working area (PDWK) of ICT for MTs teachers in the district. Bojonegoro. This type of research is a pre-experimental research design with one group preset-postest design. Data on student activities were analyzed descriptively, data on participant learning outcomes were analyzed using paired t-test and data on participants' responses to training were analyzed descriptively. The results showed: (1) The participants' activity with an average observation result was 79.14% with very high criteria; (2) the criteria for improving student learning outcomes obtained a p-value of 0.000 <0.05, stated that it can significantly improve learning outcomes; (3) The response of the participants was positive, indicated by the mean response rate of 79.14% with very high criteria.